Analisis Financial Distress Untuk Memprediksi Potensi Kebangkrutan PT. X Yang Terdaftar Di BEI - Saladin, Hendry; Oktariansyah, Oktariansyah; Sari, Novita (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p18, 2022)
Financial distress can occur in every company. If financial distress is not immediately addressed, it can lead to bankruptcy. This study aims to determine the potential for bankruptcy at PT. X is listed on the Indonesia Stock Exchange (IDX) using the Springate model, the Zmijewski model and the Grover model. The method used is a qualitative method. The research sample is a statement of financial position and profit and loss of PT. X the first quarter of 2021 - the first quarter of 2022. The results of the research from the three models used are only the Springate model which predicts the company in a potentially bankrupt condition, while the Zmijewski model and the Grover model predict the company in a non-bankrupt potential condition. Keywords: Financial Distress; Springate Model; Zmijewski Model; Grover Model